Indicadores ambientais, sociais e de governança em confinamentos de bovinos de corte - Bertho, Raul (Universidade Federal de São Carlos, 2025)
The growing demand for food has pressured the beef sector to improve production efficiency. Intensive production systems, such as feedlots, have been increasingly adopted to meet this expanding demand. Brazil is a global leader in this strategy and currently the world’s largest beef exporter. However, the sector faces growing challenges in producing sustainably, including meeting the United Nations’ Sustainable Development Goals (SDGs). Despite progress, gaps remain regarding the standardization and use of sustainability indicators that adequately reflect environmental, social, and governance (ESG) performance in beef production systems. This study aims to develop and empirically validate a set of indicators to measure ESG level in beef cattle feedlot systems. The methodology comprised three stages: (1) development of an indicator model based on a systematic literature review of ESG indicators applicable to livestock systems; (2) validation of the model using the Analytic Hierarchy Process (AHP) with a panel of experts from the beef supply chain; and (3) field application for empirical assessment of the model in small-, medium-, and large-scale feedlots. Fifteen relevant ESG themes were identified, weighted through AHP, and organized into indicators. Governance was considered the most important dimension by experts (42.6%), followed by environmental (36.1%) and social aspects (21.3%). Field results showed that large-scale operations achieved the highest overall ESG compliance (average score 9.03/10), followed by medium (7.67) and small operations (5.75). In governance, large producers scored 9.5, indicating strong organizational structure, well-defined decision-making processes, and effective control mechanisms. Environmental performance was lowest among large producers (8.44), while the social dimension had the lowest overall compliance, particularly in small feedlots (5.17). Medium producers performed best socially (8.02), reflecting greater attention to employee well-being. GHG emissions showed low compliance across all groups (20–40%), indicating common challenges in climate impact mitigation. Animal welfare, however, was widely met with high compliance across all categories. The developed model provides a practical tool for producers to manage ESG performance, assists slaughterhouses in supplier evaluation and incentive programs, and offers a foundation for public policies and regulations, fostering sustainable practices throughout the beef supply chain.
Environmental, social and governance indicators in beef cattle feedlots
Keywords: Pecuária de corte; Confinamento; Indicadores; Ambiental; Social; Governança; Sustentabilidade; Beef cattle production; Feedlot system; Indicator; Environmental; Social; Governance; Sustainability; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO; 9. Indústria, Inovação e Infraestrutura; 17. Parcerias e Meios de Implementação; 13. Ação contra a Mudança Global do Clima